2004
DOI: 10.1055/s-2004-834872
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophanes. Part LII:Ethynyl[2.2]paracyclophanes - New Building Blocks for Molecular Scaffolding

Abstract: The synthesis of seven ethynyl[2.2]paracyclophanes is described. The five diethynyl derivatives 4,5-diethynyl[2.2]paracyclophane (12), pseudo-gem-(13), pseudo-ortho-(14), pseudo-meta-(15), and pseudo-para-diethynyl[2.2]paracyclophane (16), the tetraethynyl compound 4,7,13,16-tetraethynyl[2.2]paracyclophane (17), and for comparison the mono-ethynylated hydrocarbon 4-ethynyl[2.2]paracyclophane (11) have been prepared. The structures of these new building blocks for carbon rich systems were determined by the usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Although we have separated the four isomers and used them many times for the preparation of numerous [2.2]paracyclophane derivatives (inter alia annelated derivatives [2], metal complexes [35], diethynyl derivatives [67] and preparation of ligands for chiral reagents [8–9]), we have neither described the separation of these versatile starting materials nor explained their spectroscopic and analytical data in full. With this short communication, we would finally like to remedy this omission, in particular since these compounds are also beginning to attract the attention of other research groups [67 1013].…”
Section: Introductionmentioning
confidence: 99%
“…Although we have separated the four isomers and used them many times for the preparation of numerous [2.2]paracyclophane derivatives (inter alia annelated derivatives [2], metal complexes [35], diethynyl derivatives [67] and preparation of ligands for chiral reagents [8–9]), we have neither described the separation of these versatile starting materials nor explained their spectroscopic and analytical data in full. With this short communication, we would finally like to remedy this omission, in particular since these compounds are also beginning to attract the attention of other research groups [67 1013].…”
Section: Introductionmentioning
confidence: 99%
“…Although its synthesis from the previously described ethynylaldehyde 13 [23] appears simple, we always obtained complex mixtures of products when 13 and excess 1,2-diiodobenzene ( 14 ) were subjected to Sonogashira coupling. The main product of this coupling process was the monoaldehyde 15 (i.e., the 1:1-coupling product of 13 and 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several years ago we described the preparation of various ethynyl[2.2]paracyclophanes and suggested that these compounds could be developed into useful building blocks for the construction of larger, stereochemically complex carbon frameworks (scaffolds) [2]. This prediction is clearly becoming reality, as shown by the growing use of ethynylcyclophanes as substrates for the preparation of carbon-rich organic compounds [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, unsaturated cyclophane bis(esters) undergo intramolecular photocyclization, yielding the corresponding ladderane isomers [911]. The ethynyl group is well known for its ability to undergo coupling reactions, making the pseudo-geminal bis(acetylene) 1 and its derivatives good candidates for building molecular scaffolding [1213]. The reaction between bis(acetylene) 1 and other acetylene derivatives has been reported to provide new π-bridges in [2.2]paracyclophane [14].…”
Section: Introductionmentioning
confidence: 99%